The Influence of Strategic Orientation on Family Business Survival Mediated by Innovation in Service Industry - Velly Anatasia; Willy Arafah; Bahtiar Usman (Dinasti International Journal of Management Science, 2023)
This research aimed to investigate the influence of strategic orientation on SME family businesses survival mediated by innovation in service industry. In this study, we analyze the impact of strategic orientation includes entrepreneurial orientation, market orientation, technological and orientation on the innovation of SME family businesses as well as the impact of those strategic orientations on SME family businesses survival. A total 225 owners or managers of SME family businesses participated in this study. The sample was collected based on purposive method. The respondent population of this research is all family business owners or managers located in DKI Jakarta and Tangerang area and have been running their business for at least two years and survive during Covid-19 Pandemic. To analyze the relationship among latent variables, we implemented Structural Equation Model (SEM). The results show that only market orientation has a higher direct effect on family business survival, while entrepreneurial orientation and technological orientation requires mediation role from innovation. In this study, market orientation had the highest impact on family business survival with or without mediated by innovation. The results of this study provide insight for SMEs family business owners or managers, in order to use their strategic orientations through implemented innovation to adapt unpredictable situation and crisis that emerge due to Covid-19 pandemic, in order to survive. This study was limited to the sample of business that is in service industry and located on DKI Jakarta and Tangerang only. For the further research the model can be broaden to add the role of government support for the family business survival and overspread to another location in Indonesia.